Modelling China's outbound tourist flow to the 'Silk Road': A spatial econometric approach. Issue 8 (December 2019) - Deng, Taotao; Hu, Yukun
With the ancient Silk Road as the historical background, the 'Belt and Road' initiative aims to foster common development of regional economies. Regional tourism development is an essential part of the initiative. Taking 55 countries participating in the initiative as a research sample, the article investigates the determinants and spillover effect of Chinese outbound tourist flows by spatial panel models. Furthermore, we identify different spillover paths from the perspectives of geographic and cultural proximities. The results confirm that there exist significant positive spillover effects in tourist flows among countries with geographic proximity. Meanwhile, there exist significant positive spillover effects in tourist flows among countries with cultural proximity. In addition, geographic and cultural distances between China and tourist destinations have negative impacts on Chinese outbound tourist flow.